A third era of credit theory? Endogenous money from Wolfgang Stützel's balance mechanics perspective - Christoph Ellermann; Fabian Lindner; Severin Reissl; Ruben Tarne (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
We present an introduction to the translation of a part of the stock-flow consistent (SFC) framework published by the German economist Wolfgang Stützel in 1958, which follows in this issue. While not a quantitative model, Stützel's 'balance mechanics' has some features which still stand out today when compared with contemporary SFC literature. Among these strengths is an accounting decomposition of all economic transactions along three dimensions and a careful distinction between propositions which are true at different levels of aggregation, so as to avoid fallacies of composition. We argue that 'balance mechanics' provides value added, both as a didactic tool and as a complement to formal SFC modelling exercises, since it can be used to assess the validity and coherence of economic propositions. We demonstrate this claim by translating a section on the so-called 'third stage of credit theory' in the translation that follows this introductory paper. Therein, Stützel synthesises the two opposing positions in the controversy on the causal priority of deposits versus loans in banking.
Keywords: B31; B41; B50; E51; 330; Stuẗzel; balance mechanics; endogenous money; stock-flow consistency